Pengaruh Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Studi Literatur Pada Siswa Sekolah Menengah Kejuruan - Merliana Br Simamora (Yayasan Syamil Quran Nunukan, 2024)
The high unemployment rate among vocational high school (SMK) graduates highlights a gap between vocational education and labor market demands. This study aims to examine the influence of entrepreneurial knowledge on students' interest in entrepreneurship, evaluate the role of entrepreneurship programs in schools, and identify internal and external factors affecting students' entrepreneurial interest. Using a literature review method, this research integrates findings from relevant studies published between 2020 and 2024. The analysis is conducted thematically, focusing on aspects such as entrepreneurial knowledge, motivation, self-efficacy, family environment, and support from educational programs and government policies. The findings reveal that entrepreneurial knowledge significantly influences students' interest in entrepreneurship, supported by individual motivation, self-efficacy, and a conducive family environment. Moreover, entrepreneurship programs in schools and supportive policies play a crucial role in preparing students to create independent career opportunities. This study provides a comprehensive understanding of how entrepreneurial education impacts vocational students’ entrepreneurial interest while highlighting key strategies to address existing challenges. The insights from this research are expected to serve as a reference for policymakers and educators in designing effective entrepreneurship education programs to foster students' readiness and enthusiasm for entrepreneurial ventures.